Cogan syndrome with systemic manifestations - Nataliya А. Morova; Yulia V. Arbuzova (Лечащий Врач)
Background. Cogan syndrome is a rare systemic vasculitis with variable arterial involvement. Its true prevalence is unknown. It is characterized by ocular symptoms, hearing loss, vestibular dysfunction. Cogan syndrome can be classified as typical or atypical. Typical syndrome is characterized by a combination of bilateral keratitis with hearing loss and vestibular dysfunction. Atypical syndrome includes other types of eye or hearing damage and cases when the interval separating these symptoms onset exceeds 2 years. Systemic manifestations are more common in atypical Cogan syndrome. There are different theories about the development of the disease. Currently, the most popular autoimmune theory is that Cogan syndrome is based on autoimmune vasculitis of the most vascularized layers of the eye, inner ear and other organs. The search for immune markers in Cogan syndrome led to the discovery of antibodies to antigens of the inner ear, cornea, and antiendothelial antibodies, but their diagnostic value is not great. Immune markers that allow a confident diagnosis have not yet been discovered.Objective. Report a case of the Cogan syndrome with systemic manifestations in a female patient.Results. We present the clinical case of Cogan syndrome in a 37-year-old patient. The disease was diagnosed based on the presence of acute conjunctivitis, acute bilateral sensorineural hearing loss, dizziness. These symptoms were preceded by fever, arthralgia, myalgia, diarrhea. Conjunctivitis and audiovestibular symptoms appeared at the same time. Additionally, the patient exhibited systemic manifestations such as polyserositis, pneumonitis, erosive colitis with malabsorption syndrome, abdominal lymphadenopathy, anemia, thrombocytopenia. The notable aspect of the case was a very early diagnosis (a week after the onset of the disease). This factor determined the achievement of a good and rapid response to treatment within the first week. Treatment included glucocorticoids, pulse cyclophosphamide therapy. Within a month, all symptoms were completely resolved.Conclusion. Early diagnosis and timely treatment of Cogan syndrome makes it possible to completely relieve symptoms of the syndrome and prevent deafness.